Pemanfaatan Limbah Plastik dari Polietilen Tereftalat PET sebagai Penguat pada Komposit Bermatriks Epoxy - Laksana, Alfian Hudan; Waluyo, Marhadi Budi; Murdianto, Deny; Wahyudi, Muhammad (Faculty of Engineering, Universitas Borneo Tarakan, 2024)
Public consumption of bottled drinking water continues to increase. Single use plastic bottled water is still an option, this increases plastic waste. The main cause is that plastic cannot be decomposed so it has a bad impact on the environment. Plastic waste recycling has been done to reduce plastic waste but is still in low quantities. One of the recycling processes of plastic waste bottles can be utilized as composite materials. Composite consists of elements namely matrix and filler. In this study, the composite is composed of epoxy as a matrix and plastic bottle waste as a filler. The composition of the filler used ranges from 12.5%, 15%, 17.5%, 20%. The composite was made using the hand lay-up method. The composite that had been made was tested for hardness and impact to observe its mechanical properties. From the results of the research test, it was obtained that the greater the variation of the filler used, the lower the impact strength and hardness values. The highest impact strength was 1.02 J/mm2 Joule at a variation of 12.5%. The highest data results from the hardness test in this study were at a variation of 20% of 75.33 shore D.